A-257 Use of inpatient tele-neuropsychological evaluation to assist neurological management of a complex Spanish-speaking patient in the time of COVID-19. (28th August 2020) - D, Gonzalez; C, Hung; J, McGinley; R, Facchini; D, Bronshteyn; D, Masur; E, Weiss
Abstract: Objective: The COVID-19 pandemic has impacted traditional neuropsychological practices as in-person evaluations have been postponed. Controversy and ongoing discussion remains about the validity and appropriateness of teleneuropsychology, but provider and patient risk associated with in-person testing needs to be considered when cognitive evaluation is warranted. We describe the remote evaluation of a man hospitalized with altered mental status and positive COVID-19 infection and the effectiveness of teleneuropsychology in clarifying cognition/assisting clinical management in a non-English-speaking individual with limited formal education. Method: 35 year old Spanish-speaking male with no formal education referred for inpatient neuropsychological consultation to rule in/rule out possible encephalopathy and confirm premorbid cognitive functioning. Cognitive evaluation completed using iPad and Zoom technology at bedside. Results: Tele-neuropsychology was conducted in the patient's primary language without the necessity for PPE, which enabled improved engagement. Although testing had to be modified; the environment could not be controlled; and all cognitive domains could not be evaluated—remote evaluation confirmed fluctuations and variability, both within and between tasks, with notable fluxes in attention, comprehension and speech. Results aided in the management and care of the patient. Conclusion: Tele-neuropsychological evaluation in the inpatient setting, while not a replacement for traditional in-person assessment, can play an important role in the management and care of culturally and educationally diverse patients.